Massage as a mechanotherapy promotes skeletal muscle protein and ribosomal turnover but does not mitigate muscle atrophy during disuse in adult rats. (17th March 2020) - Lawrence, Marcus M.; Van Pelt, Douglas W.; Confides, Amy L.; Hunt, Emily R.; Hettinger, Zachary R.; Laurin, Jaime L.; Reid, Justin J.; Peelor, Frederick F.; Butterfield, Timothy A.; Dupont‐Versteegden, Esther E.; Miller, Benjamin F.
Abstract: Aim: Interventions that decrease atrophy during disuse are desperately needed to maintain muscle mass. We recently found that massage as a mechanotherapy can improve muscle regrowth following disuse atrophy. Therefore, we aimed to determine if massage has similar anabolic effects when applied during normal weight bearing conditions (WB) or during atrophy induced by hindlimb suspension (HS) in adult rats. Methods: Adult (10 months) male Fischer344‐Brown Norway rats underwent either hindlimb suspension (HS, n = 8) or normal WB (WB, n = 8) for 7 days. Massage was applied using cyclic compressive loading (CCL) in WB (WBM, n = 9) or HS rats (HSM, n = 9) and included four 30‐minute bouts of CCL applied to gastrocnemius muscle every other day. Results: Massage had no effect on any anabolic parameter measured under WB conditions (WBM). In contrast, massage during HS (HSM) stimulated protein turnover, but did not mitigate muscle atrophy. Atrophy from HS was caused by both lowered protein synthesis and higher degradation. HS and HSM had lowered total RNA compared with WB and this was the result of significantly higher ribosome degradation in HS that was attenuated in HSM, without differences in ribosomal biogenesis. Also, massage increased protein turnover in the non‐massaged contralateral limb during HS. Finally, we determined that total RNA degradation primarily dictates loss of muscle ribosomal content during disuse atrophy. Conclusion: We conclude that massage is an effective mechanotherapy to impact protein turnover during muscle disuse in both the massaged and non‐massaged contralateral muscle, but it does not attenuate the loss of muscle mass.